Factors influencing missed nursing care for older people following fragility hip fracture. Issue 4 (August 2020) - Fitzgerald, Amanda; Verrall, Claire; Henderson, Julie; Willis, Eileen
Abstract: Background: Older people suffering fragility hip fractures are among the most fragile and vulnerable hospital patients. They often have complex care needs due to pre-existing and chronic conditions which may exacerbate as a consequence of surgery and hospitalisation. When deviations from best practice occur, care can be missed. Aim: To identify factors that influence missed care for the older person with a hip fracture; inform recommendations for change and highlight the need for further research to achieve best practice nursing care for older people following a fragility hip fracture. Methods: A scoping review was conducted using databases Cumulative Index to Nursing and Allied Health Literature, Medline and Scopus, using a combination of keywords. Findings: Twenty-two relevant papers published between 2010-2018 were identified illustrating areas where nursing care was missed for either patients with hip fractures, older patients or both. Discussion: This paper has reviewed literature related to nursing care for older people following a hip fracture to determine what nursing care may be missed; why it is missed and to identify strategies to improve outcomes through reducing the impact of missed nursing care for this population. Existing missed care literature usually focusses upon structural and organisational issues to the detriment of other factors. Conclusion: Missed nursing care for the hospitalised older person with a hip fracture can be organised under three broad themes: organisational factors, nurse and patient characteristics.